Peningkatan Kinerja Usahatani Hortikultura Melalui Pengembangan Pola Kemitraan Agribisnis: Studi Kasus Kelompok Tani Sidoluhur, Desa Cabeyan, Kabupaten Sukoharjo - Nimas Suci Kusuma Melati; Alifa Putri Madina; Iis Sawitri; Mayang Risti Kusuma Dewani; Ernoiz Antriyandarti; Putriesti Mandasari (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2024)
The development of horticultural farming through agribusiness partnerships can serve as a solution to farmers' limitations in managing agricultural risks. Partnerships have the potential to improve farming productivity and ensure price certainty. However, in some instances, partnership practices may give rise to issues such as dependency and weakened bargaining power for farmers. This research aims to investigate and analyze the potential for enhancing the performance of horticultural farming through the development of agribusiness partnership models in the Sidoluhur Farmers' Group, Cabeyan Village, Sukoharjo District. The research methodology employed is a descriptive case study involving five key respondents, including a lecturer from Universitas Sebelas Maret, the owner of Spesial Sambal, and farmers engaged in cultivation or responsible for the Sidoluhur Farmers' Group. The case study method allows for in-depth investigation into specific cases and facilitates the development of narratives or stories. The research findings indicate that the established partnership model is a subcontracting pattern involving three parties: the Sidoluhur Farmers' Group, PT Waroeng Spesial Sambal, and Universitas Sebelas Maret. The partnership provides market certainty for the farmers with a stable selling price. Importantly, this partnership does not create dependency on PT Waroeng Spesial Sambal, as farmers are free to market their harvests independently.